Syndrome in question - Isy Lima Peixoto; Ana Maria Carreno; Vania Mesquita Gadelha Prazeres; Caroline Albuquerque Rodrigues Chirano; Gabriel Maroja Ihara; Patricia Bandeira de Melo Akel (Sociedade Brasileira de Dermatologia, 2014)
Costello syndrome (CS) is a rare genetic disorder, first described by Costello in 1971, caused by mutations in the HRAS proto-oncogene. Clinical findings include facial dysmorphism, skin disorders, cognitive impairment, cardiac and musculoskeletal defects. There is an increased risk of malignancies in these patients, due to the proto-oncogene mutation, and also sudden death secondary to heart disease. We report a case with characteristic phenotype, highlighting the peculiar skin changes.